Fruit size and sphape diversity in Solanum aethiopicum: Fruit size and sphape diversity in Solanum aethiopicum - TAIWO, ADEKUNLE; Innocent; adamu, J.T; janah peter; adekoya, M; Aremu (Journal of Agricultural Sciences (Belgrade), 2021)
Scarlet eggplant (Solanum aethiopicum [L.]) is an indigenous, underutilized fruit vegetable in Africa. Preference for fruit shape and size is high among growers and consumers. Fruit metric traits are important for improvement in yield. Fruit metric descriptors are important contributors to variation, phenotypic and genotypic variation, and heritability. However measurement of these traits are cumbersome and subjective. Forty-three accessions were evaluated in 2016 and 2017. At maturity, 5 fruit were randomly harvested from each accession, digitalized and processed with Tomato Analyzer software. Sixteen fruit metric traits were automatically generated and submitted for analysis of variance and multivariate analysis. The accessions differed for fruit size and shape due to genetic make-up. Fruit metric traits variation among S. aethiopicum groups were less influenced by environment. The cv. Gilo group have oblong fruit, the cv. Shum group are circular and ovoid; cv. Kumba group are less circular, lobed and flattened. AE/113 (C3), FUO 1 (C1) and FUO 5 (C2) ‘Gilo’ group are promising for fruit size. There was phenotypic plasticity and overlap for fruit metric traits between the ‘Gilo’ and ‘Shum’ groups due to a common genome. The Tomato analyzer software was able to discriminate accessions based on fruit phenomic traits, and the information could be used to establish commonalities between groups.